(3TQM YeOI GdMGaX hYOI GddGaXs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3gPg JfHjgGJ eNJUQI jSJYGf HgG Ydi eG JVefJg ebOeJj GdehSheI HYeOI GdMGaX hYOI GddGaX s
(3BNQgG (B:s
(3eKd GdMQjb UGOa GdbUHG haj GdGNJjGQ bdjdkG efg KHhJ gGA GdScJ aj hUd JGdjg hfXGFQg hGddg CYde ced GdcJGH s
(3ajg VHWs
(3hHgG fXGe GdJYbjHIs
(3HChdgG agQS Hbde MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdfMhs